Penyusunan Buku Saku Keanekaragaman Hayati dengan Uji Keterbacaan sebagai Evaluasi Konten - Saputra, Aliman (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This research aims to compile a pocketbook on biodiversity that is effective and easy for students to understand. In the process of its preparation, a readability test of the pocketbook was conducted to evaluate the extent to which the book can be accepted and understood by readers. This research is a quantitative descriptive study aimed at measuring the readability level of the pocketbook through a readability test instrument. The readability test was conducted by involving 15 students as respondents, which resulted in a readability score of 89%. These results indicate that the biodiversity pocketbook has a very good level of readability. Based on the research results, it can be concluded that this pocketbook is categorized as very interesting for students, making it an effective source of information in learning about biodiversity.